Neural 3D Scene Reconstruction with the Manhattan-world Assumption - Guo, Haoyu; Peng, Sida; Lin, Haotong; Wang, Qianqian; Zhang, Guofeng; Bao, Hujun; Zhou, Xiaowei (Proceedings (IEEE Computer Society Conference on Computer Vision and Pattern Recognition. Online), 2022)
This paper addresses the challenge of reconstructing 3D indoor scenes from multi-view images. Many previous works have shown impressive reconstruction results on textured objects, but they still have difficulty in handling low-textured planar regions, which are common in indoor scenes. An approach to solving this issue is to incorporate planer constraints into the depth map estimation in multiview stereo-based methods, but the per-view plane estimation and depth optimization lack both efficiency and multiview consistency. In this work, we show that the planar constraints can be conveniently integrated into the recent implicit neural representation-based reconstruction methods. Specifically, we use an MLP network to represent the signed distance function as the scene geometry. Based on the Manhattan-world assumption, planar constraints are employed to regularize the geometry in floor and wall regions predicted by a 2D semantic segmentation network. To resolve the inaccurate segmentation, we encode the semantics of 3D points with another MLP and design a novel loss that jointly optimizes the scene geometry and semantics in 3D space. Experiments on ScanNet and 7-Scenes datasets show that the proposed method outperforms previous methods by a large margin on 3D reconstruction quality. The code and supplementary materials are available at https://zju3dv.github.io/manhattan_sdf.